HUBUNGAN KECERDASAN SPIRITUAL DAN EMOSIONAL DENGAN KINERJA GURU - Helfia Helfia (INSTITUT AGAMA ISLAM NEGERI METRO, 2021)
Spiritual and emotional intelligence is one of the most important components in tecacher’s performance. The teacher should be able to perform the planning of teaching and learning process, implementing teaching and learning process, evaluating learning process and implementing the accountable follow-up, therefore the teacher’s performance will be better. In implementing the performance, the teacher must have good spiritual and emotional intelligence. The aim of the study is to show the relationship between spiritual intelligence and emotional intelligence and the teacher’s performance in all of SDIT metro city.The hypothesis proposed is; There is a positive and significant relationship between the Relationship of Spiritual Intelligence and Emotional Intelligence and the teacher’s performance either individually or collectively. This research is designed quantitatively with the research population are all teachers who are in SDIT of Metro city with total number is 93 teachers.The sampling ofthe study was done with the formula from isaac and michael, which the table with the level of error 10%. The instrument usedLikert scale model questionnaire that has been tested for its validity and reliability.The first and second hypotheses were tested with partial correlation techniques, and the third used multiple correlation techniques. The results showed that (1) the achievement level of spiritual intelligence score of 76.31% from ideal maximum score and included enough categories.Spiritual intelligence contributes significantly to the teacher's performance of 17.70%.(2) The achievement level of Emotional Intelligence score of 79.97% of the ideal maximum score and including enough category. Emotional intelligence contributes significantly to teachers' performance of 14.40%.(3) Level of achievement of teacher performance score equal to 77,39% from ideal maximum score and included enough category. Spiritual intelligence and emotional intelligence together contribute significantly to teacher performance by 39.50%. The study found that the two predictor variables studied individually and collectively contributed significantly to teacher performance. Therefore these two predictors need more attention to improve teacher performance.Thus, the performance of teachers will be better with the increase of spiritual and emotional intelligence.